AB0048 Proinflammatory Macrophage Polarisation in Rheumatoid Arthritis and its Regulation by the Histone Methyltransferase EZH2. (9th June 2015) - Trenkmann, M.; Linehan, E.; Canavan, M.; Veale, D.; Fearon, U.
Abstract : Background: Macrophages (MΦ) are tissue-resident innate immune cells central to the pathogenesis of rheumatoid arthritis (RA) that produce inflammatory cytokines and degradative enzymes in great abundance. MΦ polarise along a spectrum of classical (M1) to alternative (M2) activation gearing their function towards proinflammatory to regulatory/wound-healing/proangiogenic activities. Differentiation and polarisation are epigenetically regulated and an associated imbalance might contribute to chronic inflammation in RA. Objectives: To examine MΦ polarisation and epigenetic regulation in RA. Methods: Monocyte-derived MΦ (MDM) were obtained by in-vitro differentiation from RA and healthy control (HC) peripheral blood monocytes using M-CSF. THP-1 monocytes were differentiated into MΦ using PMA. M0 MΦ were polarised with LPS+IFNγ (M1) or IL-4 (M2) or cultured with RA synovial fluid (SF). Additionally, MΦ were transfected with siRNA for the histone methyltransferase Enhancer of Zeste homologue 2 (EZH2). MΦ polarisation and activation were analysed by flow cytometry and gene expression by quantitative real-time PCR and Western blot. Results: All MDM analysed were >90% CD68 + confirming efficient in-vitro MΦ differentiation. M1-polarised MDM showed induction of M1 markers (CD40, CD64) and the activation marker CD80 while M2-polarised MDM upregulated CD206. Similar results were obtained for THP-1 MΦ (increase in CD40 + and CD80 + cells by LPS+IFNγ, increase in M2 marker CD209 under IL-4). 71±16% of RA M0 MDM were positive for CD64 as opposed to 28±14% in HC (p<0.005); this difference was maintained under M1 polarisation (87±6% vs. 59±22% CD64 +, p<0.05) indicating an intrinsic shift towards a proinflammatory M1 phenotype in RA. In support of this, HC M0 MDM expressed higher levels of proangiogenic VEGF than RA M0 MDM (2.5-fold, p<0.01). The histone 3 lysine 27 (H3K27) demethylase JMJD3 was significantly induced in both M1- and M2-polarised MDM (3.4±0.9- and 2.6±0.5-fold, p<0.05) whereas the H3K27 methyltransferase EZH2 was upregulated only in M1-polarised MDM (11.4±1.7-fold, p<0.005) which was confirmed at the protein level by Western blot. Silencing of EZH2 reduced the numbers of CD64 + and CD40 + cells among M1-polarised MDM as well as CD206 + cells among M2 MDM (RA and HC). Similarly, among THP-1 M1 MΦ, reduced numbers of CD40 + and CD80 + cells were observed upon siEZH2 transfection. Furthermore, EZH2 siRNA significantly inhibited the induction of IL6 and IL1B in M1 MDM but increased the expression of IL1B in M0 MDM (p<0.05). Finally, culture of M0 MDM with RA SF induced an M1-M2-intermediate state with an increase in the numbers of CD40 +, CD64 + and CD206 + cells (p<0.01). Conclusions: We demonstrate skewing of RA MDM towards a proinflammatory M1-like phenotype, differential induction of EZH2 and JMJD3 in M1- and M2-polarised MDM and a hybrid M1-M2 phenotype of MDM exposed to an RA synovial environment. Our data underline the complexity of macrophage polarisation in RA and the importance of epigenetic regulation in this process. Disclosure of Interest: None declared